PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DENGAN MEDIA KARTU BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Nopiawan, Fidy Dwi; Sudin, Ali; Kurnia, Dadang (Jurnal Pena Ilmiah, 2017)
SocialÂ  studies Learning on the material of ethnic and cultural diversity in Indonesia In grade IV A SDN Cimalaka II Cimalaka Subdistrict Sumedang Regency there is a problem where students difficulty in receiving the materials. In the learning process the teacher does not design the model and learning media, So that learning is not meaningful and student learning outcomes are low. The strategy used in overcoming this problem is by applying the two stay two stray learning model with the media of cultural card. The research method used is classroom action research of spiral model and expected to improve student learning outcomes. This study was conducted in three cycles, the increase of student learning outcomes in the first cycle reached 55%, 70% cycle II, and 90% 90% cycle III. Therefore, it can be concluded that the learning by applying the learning model of two stay two stray with the media of cultural card can uplift student learning outcomes on the material of ethnic and cultural diversity in Indonesia in class IV.